The Effect of Communication, Motivation, and Work Discipline on Job Satisfaction of Employees in The Environmental Service of Balikpapan City - Ramadhana, Fitri; Ariani, Misna; Arrywibowo, Imam (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study was to determine the effect of Communication, Motivation, and Work Discipline on Job Satisfaction of Balikpapan City Environmental Service Employees. In this study, there was a population of 74 employees and a sample of 60 respondents . The method used in this study was a statistical test with primary data from the distributed questionnaire . Data analysis used SmarPLS. The results of the study showed that the variables partially Communication and work discipline have a positive influence, while motivation does not have an influence on employee job satisfaction.